Awareness About Effects of Consumption of Tobacco and Tobacco Products in Patients with Potentially Malignant Disorders and Oral Cancer - Bhoi, Pooja; SR, Ashwinirani; Mahajan, Madhura; Ka, Kamala (Journal of Neonatal Surgery, 2025)
Introduction: Tobacco use remains one of the leading preventable causes of morbidity and mortality worldwide. In India, its extensive cultural acceptance in various forms has led to a high burden of tobacco-related diseases, including oral potentially malignant disorders (OPMD) and oral squamous cell carcinoma (OSCC). Despite the known health risks, awareness about the oral consequences of tobacco use is often limited. Early recognition of symptoms and improved awareness among at-risk individuals are crucial for preventing progression from OPMD to cancer. This study assesses awareness among patients diagnosed with OPMD and oral cancer. Methodology: A cross-sectional, questionnaire-based survey was conducted at the Department of Oral Medicine and Radiology, Krishna VishwaVidyapeeth, Karad. Ethical clearance was obtained (Protocol No. 210/2023-2024). A structured, validated questionnaire was distributed via Google Forms to 101 patients diagnosed with potentially malignant disorders or oral cancer, who consented to participate. Data on demographic details, tobacco use patterns, awareness about tobacco-related health risks, and knowledge about cessation services were collected. Responses were recorded in Microsoft Excel and analyzed using SPSS version 20. Descriptive statistics summarized awareness levels, and inferential analyses examined correlations between demographics and awareness. Results: Among 101 participants, 99% reported active tobacco use. About 50.5% were aware that tobacco consumption predisposes to oral cancer, and 61.4% recognized that increased frequency and duration elevated cancer risk. Awareness that tobacco also causes lung cancer was noted in 69% of respondents. Regarding clinical signs, 55.4% identified proliferative mass and 51.5% identified non-healing ulcers as manifestations of oral cancer. Awareness of tobacco cessation counseling services was present in 67.3% of patients, with 64.4% believing counseling to be effective. Efforts to quit tobacco had been made by 58.4% of participants, and 74.2% acknowledged the role of family support in cessation. Although moderate awareness was observed, substantial gaps in knowledge and behavior change were evident. These findings highlight the critical need for targeted education and intervention efforts among high-risk groups. Conclusion: This study reveals moderate awareness about the harmful effects of tobacco among patients with potentially malignant disorders and oral cancer. However, the gap between awareness and actual behavior change persists. Strengthening individual-level counseling, enhancing community engagement, and leveraging family support systems are essential to promote successful tobacco cessation. Future studies involving larger, diverse populations and clinical correlation are needed to design more effective preventive strategies and interventions.